Slow lenalidomide desensitization protocol for patients with multiple myeloma: case series from a single center. Issue 13 (10th November 2019) - Yau, Patrick; Jimenez-Zepeda, Victor H.; Bailey, Kyla; Duggan, Peter; Tay, Jason; Bahlis, Nizar J.; Neri, Paola; McCulloch, Sylvia
Abstract: Lenalidomide is an immunomodulatory agent that belongs to a family of IMiDs used to treat multiple myeloma. Hypersensitivity and skin reactions are adverse effects of lenalidomide that may lead to discontinuation of its use for multiple myeloma making them contraindicated to other IMiD therapies. Desensitization protocols have been developed to desensitize patients to lenalidomide skin reaction and rash. We report a case series of 5 patients undergoing slow lenalidomide desensitization protocol in an outpatient cancer center setting. Four of the five patients were able to be successfully desensitized to lenalidomide. We also demonstrate safety of using slow lenalidomide desensitization while on combination therapy for control of multiple myeloma.